Dynamic simulation model of Fiber Optical Current Transformer considering error factors. (September 2019) - Li, Dengyun; Li, He; Zhang, Dandan; Mo, Shi; Chai, Yongfeng
Abstract: The paper studies and establishes the dynamic model of fiber optical current transformer by MATLAB. The equivalent model of FOCT's digital closed loop control system is created by reasonably simplifying deviation and feedback of FOCT. By analyzing the four components of FOCT's main sources of error, 10 factors that cause FOCT measurement errors are obtained. Then the variable 10 error parameters are introduced into the model to establish a dynamic model of fiber optical current transformer considering the error factor. The model can evaluate the performance of the fiber optical current transformer by using the variable FOCT's error parameters, Also, model dynamically combines the FOCT's related parameters and environmental factors with the transformer's transfer characteristics and reflects the influence of FOCT error factors on FOCT performance.